2010
DOI: 10.1007/s12195-010-0127-x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Primary Cilia in Mesenchymal Stem Cell Differentiation: A Pivotal Switch in Guiding Lineage Commitment

Abstract: Primary cilia are sensory organelles that have been shown to play a critical role in lineage commitment. It was our hypothesis that the primary cilium is necessary for chemically induced differentiation of human mesenchymal stem cells (MSC). To investigate this, polaris siRNA was used to inhibit the primary cilia and the mRNA levels of transcription factors Runx2, PPARγ were measured by RT PCR as markers of osteogenic, adipogenic and chondrogenic differentiation, respectively. MSCs with inhibited primary cilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 19 publications
5
102
2
Order By: Relevance
“…In addition, it was shown that while cilia are present in differentiating pre-adipocytes, cilia are lost during differentiation and mature adipocytes are non-ciliated cells [132]. Albeit transient, the presence of a primary cilium during adipocyte differentiation appears to be important since mesenchymal stem cells (MSCs) require the presence of primary cilia to differentiate toward the adipogenic lineage [133]. Moreover, Wnt and Hedgehog receptors, pathways known to regulate adipogenesis, are present in these transient cilia of differentiating pre-adipocytes [132].…”
Section: Adipogenesis Defects In the Etiology Of The Bbs Related Obesitymentioning
confidence: 99%
“…In addition, it was shown that while cilia are present in differentiating pre-adipocytes, cilia are lost during differentiation and mature adipocytes are non-ciliated cells [132]. Albeit transient, the presence of a primary cilium during adipocyte differentiation appears to be important since mesenchymal stem cells (MSCs) require the presence of primary cilia to differentiate toward the adipogenic lineage [133]. Moreover, Wnt and Hedgehog receptors, pathways known to regulate adipogenesis, are present in these transient cilia of differentiating pre-adipocytes [132].…”
Section: Adipogenesis Defects In the Etiology Of The Bbs Related Obesitymentioning
confidence: 99%
“…In kidney epithelial cells, this complex is essential for sensing fluid flow in the developing kidney and orchestrating proper cell division (53). Mesenchymal stromal cells and mature cells of the osteoblast-osteocyte lineage also possess primary cilia (39,54), and a number of the structural proteins of the primary cilium have been shown to play a role in the regulation of BMD and osteoblast function (55,56). Additionally, inactivation of Pkd1 globally (39,57) and in osteoblasts (58) leads to osteoblast dysfunction, decreased bone formation rates, and osteopenia.…”
Section: Figurementioning
confidence: 99%
“…Pkd1 and Pkd2 may thus possess mechanical force-independent functions at embryonic stages, during growth, and into adulthood. Knockdown of the primary cilia protein, Polaris, resulted in abrogation of Runx2 (45) and since primary cilia are also present in the dental pulp, it is possible that the mechanical force-independent function of Pkd1 and Pkd2 is related to primary ciliary function.…”
Section: Mechanical Stress-independent Pkd1/pkd2 Functionmentioning
confidence: 99%